RANCANG BANGUN MESIN PENGGILING BIJI JAGUNG - Ramdani, Rizki; Saleh, Agus; Julkifli, Kiki (Jurnal TEDC; Vol 17 No 3 (2023): JURNAL TEDCDO - 10.70428/tedc.v17i3.741, 2023)
Corn is a superior commodity owned by Indonesia. Apart from being a staple food, corn kernels are also used as chicken feed by grinding them using a grinding machine. But the processing of corn as animal feed is still relatively expensive. Breeders usually process corn to the mill because they don't have a grinding machine. Meanwhile, buying a grinding machine is not cheap. So to increase productivity and effectiveness in the livestock sector, it is necessary to develop technology or tools in this field. One of the technological developments that can be applied to this sector is the use of grinding machines for corn kernels. We made this machine with the aim of increasing efficiency and saving on animal feed costs. The design of this machine is carried out through the process of designing, selecting and calculating components, the stages of making and assembling the whole, as well as testing the machine. The machine was designed using Autodesk Inventor software to help design the whole. The control and electrical systems are designed using the Simurelay application. This machine has specifications of 250 watt motor power, 712 RPM rotation and 3.29 Nm torque which is capable of grinding dry corn kernels up to 30 kg/hour.